Tunisian Newborn's Cord Blood: Reference Values of Complete Blood Count and Hemoglobin Fractions - Zitouni, Sana; Bouatrous, Emna; Laabidi, Ons; Boudrigua, Imen; Chaouachi, Dorra; Saidani, Naima; Kraiem, Imen; Ayachi, Amira; Abbes, Salem; Mourali, Mechaal; Menif, Samia; Ouragini, Houyem (American Journal of Perinatology, 2020)
Objective This study was aimed to establish local reference values for hematological indices and hemoglobin (Hb) fractions in umbilical cord blood (UCB) for the northern population of Tunisia.Study Design Our study included full-term newborns by vaginal deliveries. Hematological parameters were collected using an automated blood cell counter. The amounts of Hb fractions were measured by capillary electrophoresis of Hb. Statistical analysis was performed using R software.Results A total of 328 cord blood samples were analyzed. Among them, 154 (male: 44.8%, female: 55.2%) were used to establish reference values. The normal reference values of complete blood count (CBC) and Hb fractions were calculated. Mean neonatal Hb was 14.75 ± 2.26 g/dL. Gestational age affects the expression of CBC values as red blood cell (RBC), Hb, hematocrit (Hct), mean corpuscular volume (MCV), white blood cell (WBC), and the Hb profile. Umbilical blood hemogram parameters and Hb profile are affected by the environment; higher in newborns from urban regions but not affected by gender ratio.Conclusion Reference ranges of normal CBC indices and Hb fractions have been successfully established in Tunisian neonates' UCB. Our data suggest reference values that could be useful for neonatal patients' laboratory results and clinical interpretation.Key Points
Keywords: reference values; complete blood count; hemoglobin fractions; Tunisian newborn's cord blood